Crosstalk between myocardial autophagy and sterile inflammation in the development of heart failure - Jialing Tang; Eddie Tam; Erfei Song; Aimin Xu; Gary Sweeney (Autophagy Reports, 2024)
Heart failure, a leading driver of global mortality, remains a topic of intense contemporary research interest due to the prevailing unmet need in cardiometabolic therapeutics. Numerous mechanisms with the potential to influence the onset and development of heart failure remain incompletely understood. Firstly, myocardial autophagy, which involves lysosomal degradation of damaged cellular components, confers context-dependent beneficial and detrimental effects. Secondly, sterile inflammation may arise following cardiac stress and exacerbate the progression of heart failure. Inflammation changes in a temporal manner and its onset must be adequately resolved to limit progression of heart failure. Mitochondria are an important factor in contributing to sterile inflammation by releasing damage associated molecular patterns (DAMPs) including mitochondrial DNA (mtDNA). Accordingly, this is one reason why the selective autophagy of mitochondria to maintain optimal function is important in determining cardiac function. In this review, we examine the increasing evidence suggesting crosstalk between autophagy and sterile inflammation together with their role in the development of heart failure. In particular, this is exemplified in the preclinical models of ischaemia/reperfusion injury and pressure overload induced heart failure. We also highlight potential therapeutic approaches focusing on autophagy and addressing sterile inflammation, aiming to enhance outcomes in heart failure.